Cation-mediated gelation of the fucose-rich polysaccharide FucoPol: preparation and characterization of hydrogel beads and their cytotoxicity assessment. Issue 2 (22nd January 2021) - Fialho, Letícia; Araújo, Diana; Alves, Vitor D.; Roma-Rodrigues, Catarina; Baptista, Pedro V.; Fernandes, Alexandra R.; Freitas, Filomena; Reis, Maria A. M.
Abstract: This study describes for the first time the iron- and copper-mediated gelation of FucoPol, fucose-rich bacterial polysaccharide. The ability of FucoPol to gel in the presence of metal cations, including iron(III) and copper(II), was used for the preparation of hydrogel beads. Iron mediated the formation of stable and not cytotoxic gel beads, while copper resulted in fragile and cytotoxic ones. Copper-mediated beads coated with an iron-mediated gel layer were more stable and had reduced cytotoxicity. The resulting polymeric structures had differing morphology, physical properties and cytotoxicity, which support their use in several applications, including biomedicine, agriculture and bioremediation. Graphical Abstract: